2012
DOI: 10.4067/s0717-75182012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment of Children and Teenagers With Down Syndrome and Congenital Cardiopathy

Abstract: The aim of this study was to analyze the nutritional status of patients with Down Syndrome (DS) and congenital heart defect (CHD). A transversal study which assessed the nutritional profile of DS and CHD patients between 0 and 18 years of age was done. Weight and stature, both at birth and current were considered. A total of 98 patients, 56% female were analyzed. Prevalence of low weight, overweight and low stature at the current anthropometric data (CAD) was 30%, 22% and 17%, respectively. There was a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(32 reference statements)
0
3
0
2
Order By: Relevance
“…The present study reinforced weight problems of overweight and obesity in 10.3% each, and underweight in 7.7% participants when compared with the DS growth charts. Results from Rodrigues et al [31] also found that 22% of DS participants were overweight while 30% had low weight. Earlier, Fernhall et al [32] showed that 33.3% of the adolescents with DS were overweight, 33.3% were malnourished and 33.3% were well-nourished.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study reinforced weight problems of overweight and obesity in 10.3% each, and underweight in 7.7% participants when compared with the DS growth charts. Results from Rodrigues et al [31] also found that 22% of DS participants were overweight while 30% had low weight. Earlier, Fernhall et al [32] showed that 33.3% of the adolescents with DS were overweight, 33.3% were malnourished and 33.3% were well-nourished.…”
Section: Discussionmentioning
confidence: 96%
“…The origin of obesity in the population with DS should not be entirely attributed to the syndrome itself [7]. The potential causes of obesity may include slower basal metabolic rate, the compulsive feeding due to difficulty in chewing, and the general hypotony of the muscles causing less satiation after meals resulting in overeating [31]. Previous study [34] estimated that up to 80% of the children with DS compared to 25% typical population have difficulties related to food or feeding.…”
Section: Discussionmentioning
confidence: 99%
“…This was different from the study by Osaili et al, 32 who found that only 7.7% were underweight in relation to DS charts. However, Senna Rodrigues et al 33 found that 30% of DS participants were underweight. This may be explained by history of repeated hospitalization, ICU admissions, CHD, and respiratory infections among our study population.…”
Section: Dropped Patientsmentioning
confidence: 97%
“…Status gizi lebih yang terjadi pada anak DS harus dicegah karena dapat memperburuk kondisi kesehatan. Kondisi overweight pada anak DS merupakan faktor yang menyebabkan berbagai masalah kesehatan, seperti penyakit jantung dan muscular hypotonia (Senna Rodrigues et al, 2012;Rahmawati, 2016).…”
Section: Artikel Pengabdianunclassified